The Philippine islands, 1493-1898 (Bank of the Philippine Island, 2000)
Re-issue of the monumental work of James A. Robertson & Emma Helen Blair, in 55 volumes, published in 1903. Explorations by early navigators, descriptions of the islands and their peoples, their history and records of the catholic missions, as related in contemporary books and manuscripts, showing the political, economical, commercial and religious conditions of those islands from their earliest relations with European nations to the close of the 19th century.